Building an Oral Endoscope for Use in Equine Oral Examination and Treatment. (March 2017) - Dotzel, Allison Rita; Baratt, Robert M.
The use of oral endoscopy can be very beneficial in that it helps the clinician to perform a more thorough oral examination. However, due to the high cost, most commercially available equine oral endoscopy systems have been out of reach for clinicians who practice equine dentistry outside a large hospital setting. This article details how to set up an oral endoscopy system that can be used on equine patients either in an ambulatory practice or in a hospital setting. The system is more cost-effective than most other systems currently on the market without sacrificing functionality or image quality. The oral endoscope can be wirelessly integrated with a handheld tablet device or larger monitor for real-time viewing of images. It also has the ability to obtain high-resolution digital images and videos that can be easily incorporated into the patient's medical record. Incorporation of this system into equine practices has the potential to provide improved care for dental patients and to help overcome some of the inherent challenges of equine dentistry.